Current Management of Traumatic Macular Holes - Wu Liu; Andrzej Grzybowski (Journal of Ophthalmology)
Traumatic macular hole (TMH) is not a rare clinical condition, especially in young population. Its prognosis is of complexity and uncertainty, with a relatively high rate of spontaneous closure in some cases. Modern vitrectomy surgery plays an important role in the treatment of TMH, although the functional outcomes may be compromised by the concomitant retinal pathologies. Decision-making about the time of vitrectomy, especially in pediatric patients, remains to be clarified further.